From blood development to disease: a paradigm for clinical translation - Monica J. Justice; Julija Hmeljak; Vijay G. Sankaran; Merav Socolovsky; Leonard I. Zon (The Company of Biologists, 2020)
Translating basic research to the clinic is a primary aim of Disease Models & Mechanisms, and the recent successes in hematopoiesis research provide a blueprint of how fundamental biological research can provide solutions to important clinical problems. These advances were the main motivation for choosing hematopoiesis disorders as the focus of our inaugural meeting, 'Blood Disorders: Models, Mechanisms and Therapies', which was held in early October 2019. This Editorial discusses the reasons for and the challenges of interdisciplinary research in hematopoiesis, provides examples of how research in model systems is a key translational step towards effective treatments for blood disorders and summarizes what the community believes are the key exciting developments and challenges in this field.